King Hit - Lycos, Tom (Zeal Theatre Collection., 2018)
It's Tula's birthday party and the theme is a Blues Brothers Pizza Night. Heaps of people arrive, the music is pumping and everyone is having a great time. When Tula's parents leave the party, things change. Two boys begin a feud and what starts as a bit of fun quickly escalates into an alcohol-fuelled war reaching a shocking climax.